(untitled) (Bangladesh Medical Journal, 2024)
Cytomegalovirus (CMV) associated Biliary atresia (BA) is one of the clinical classification of Biliary atresia (BA). There is a hypothesis that CMV IgM positive BA is a clinically different entity and prognosis is poor. The aim of this study was to evaluate the clinical and biochemical parameters of CMV IgM and CMV IgG positive BA in one to six month old infants and their relation with serological titer. This cross-sectional study was carried out from January 2019 to June 2022 in the department of Pediatric Gastroenterology and Nutrition, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. A total of 48 infants were included in this study as study subject who were diagnosed as biliary atresia with positive CMV IgM & CMV IgG. After taking written informed consents data were taken from parents or legal guardians by using a structured questionnaire. Data were analyzed by statistical package for social sciences (SPSS), version- 23. Majority of the cases (58.3%) were in 2-4 month of age group, 70.8% were male and male-female ratio was almost 2.5:1. Regarding birth history most of the infants (95.8%) were term baby and two-third (66.7%) of them was appropriate for gestational age (AGA). This study observed the onset of jaundice among the infants, here 60.4% of them detected jaundice jaundice within 7 days, 22.9% within 7-14 days and 16.7% after 14 days. About three fourth (73%) of infants presented with intermittent pale stool and more than one-fourth (27%) had persistent pales tool. One fourth 12(25%) patient had features of coagulopathy. The mean of total bilirubin, direct bilirubin, alanine transaminase (ALT) and gamma-glutamyl transpeptidase (GGT ) were 11.89±4.0, 8.27±3.42, 162.67±103.09 and 669.46±543.57 respectively; The mean of the titers of CMV IgM and CMV IgG were 50.84±33.09 and 82.40±53.79 respectively. The prolong international normalised ratio (INR ) was in 30.8% of infants and mean INR was 2.44±2.54. Study finds that CMV IgM titer level was correlated with total bilirubin (r=-0.256; p<.05) and direct bilirubin (r=-0.365; p<.05); where CMV IgG titer level was correlated with age (r=-0.362; p<.05) and INR (r=0.271; p<.05). It may be concluded as increase in age would increase titer of IgG and increase in titer of IgG is associated with increase coagulopathy. Elevated levels of CMV IgM titer correlated with bilirubin level or cholestasis. Bangladesh Med J. 2023 Jan; 52(1): 12-17